Peace in world history - Stearns, Peter N., author.
1 online resource (209 pages)
Keywords: "In Peace in World History, Peter N. Stearns examines the ideas of peace that have existed throughout history, and how societies have sought to put them into practice. Beginning with the status of peace in early hunter-gatherer and agricultural societies, and continuing through the present day, the narrative gives students a clear view of the ways people across the world have understood and striven to achieve peace throughout history. Topics covered include: Comparison of the 'pax Romana' and 'pax Sinica' of Rome and China, concepts of peace in Buddhism, Christianity, and Islam, and their historical impact, the place of peace in the periods of expanding empires, the emergence, starting in the 19th century, of formal schemes to promote peace amid increasingly destructive technologies for warfare. Moving away from the view of history as a series of military conflicts, Peace in World History offers a new way of looking at world history by focusing on peace. Showing how concepts of peace have evolved over time even as they have been challenged by war and conflict, this lively and engaging narrative enables students to consider peace as a human possibility"--